Analyzing the effects of peak to average power ratio and digital predistortion in orthogonal frequency division multiplexing (OFDM) systems - Varahram, Pooria; Mohd Ali, Borhanuddin (Academic Journals, 2011)
Dummy sequence insertion (DSI) and partial transmit sequence (PTS) are two existing distortionless peak to average power ratio (PAPR) reduction techniques that have been proposed for orthogonal frequency division multiplexing (OFDM) systems. Both DSI and PTS have drawbacks. In DSI, increasing the number of dummy sequence decreases the transmission efficiency (TE) and in PTS, the complexity increases when the number of subblock increases. The DSI-PTS scheme has less complexity while the PAPR reduction is even better than PTS and DSI. Simulation and results are presented for IEEE 802.16-2004 standard. The Saleh model power amplifier is applied to show the effects of output spectrum in OFDM systems.